PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI BANGUN RUANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN TAMANSARI 1 - Nur Afifah Ramadhanti; Didit Yulian Kasdriyanto; Shofia Hattarina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low student learning outcomes in solid geometry material because the learning process still used conventional media that were less capable of visualizing three-dimensional objects realistically. This study aimed to develop Augmented Reality-based learning media on solid geometry material that is valid, practical, and effective in improving the learning outcomes of fourth grade students at SDN Tamansari 1 Probolinggo Regency. This study used the Research and Development (R&D) method with the ADDIE development model consisting of analyze, design, development, implementation, and evaluation stages. The research subjects consisted of material experts, media experts, fourth grade teachers, and fourth grade students of SDN Tamansari 1 Probolinggo Regency. Data collection techniques used observation, interviews, validation questionnaires, practicality questionnaires, and pre-test and post-test learning outcome tests. The data analysis techniques used were qualitative and quantitative data analysis. The results showed that the Augmented Reality learning media obtained a validity score from material experts of 93.18% and media experts of 92.5%, with an average of 92.84%, which was categorized as very valid. The practicality level of the media obtained a percentage of 97.5% with a very practical category. The effectiveness of the media was shown through the improvement of students’ learning outcomes with a learning completeness percentage reaching 100%. Based on these results, it can be concluded that the Augmented Reality learning media on solid geometry material is very valid, practical, and effective in improving the learning outcomes of fourth grade students at SDN Tamansari 1 Probolinggo Regency.